Chewing lice (Insecta: Phthiraptera) associated with vertebrates in Mexico - Sánchez-Montes, Sokani; Colunga-Salas, Pablo; Álvarez-Castillo, Lucía; Guzmán-Cornejo, Carmen; Montiel-Parra, Griselda (Zootaxa, 2018)
The chewing lice (Insecta: Phthiraptera: Amblycera and Ischnocera) of Mexico have been little studied and many publications include isolated records. This paper summarizes current knowledge of chewing lice recorded from Mexico resulting from an exhaustive search of the literature published from 1866 to 2017. We found 342 louse species associated with 206 bird and 28 mammal species. As a result, we provide a checklist of the chewing lice recorded from Mexico, including a host-parasite list and their geographical distribution within the country.